2015
DOI: 10.7883/yoken.jjid.2014.327
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characteristics and Antibiotic Resistance Patterns among Various Phylogenetic Groups of Uropathogenic <i>Escherichia coli</i> Isolates

Abstract: SUMMARY:The aim of this study was to determine the resistance patterns of uropathogenic Escherichia coli (UPEC) isolates and to investigate the frequency of several virulence genes, including fimH, papA, hlyD, cnf-1, sitA, and tsh, among various phylogenetic groups of UPEC isolates. A total of 85 E. coli isolates were recovered from urine samples from outpatients with a clinical diagnosis of uncomplicated urinary tract infections. A molecular approach to examine the antimicrobial resistance patterns was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
5
17
2
1
Order By: Relevance
“…These strains were mainly associated with phylogenetic groups, B2 and D as described other studies; however, they also have been associated with phylogenetic group A (Ejrnæs et al, 2011; Zhao et al, 2015). These UPEC strains could be considered community strains with predisposing factors that facilitate UTIs in immunocompromised patients, as previously reported (Derakhshandeh et al, 2015; Rodrigues et al, 2015). UPEC strains of Mexican origin are mainly associated with phylogenetic group B2 (López-Banda et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These strains were mainly associated with phylogenetic groups, B2 and D as described other studies; however, they also have been associated with phylogenetic group A (Ejrnæs et al, 2011; Zhao et al, 2015). These UPEC strains could be considered community strains with predisposing factors that facilitate UTIs in immunocompromised patients, as previously reported (Derakhshandeh et al, 2015; Rodrigues et al, 2015). UPEC strains of Mexican origin are mainly associated with phylogenetic group B2 (López-Banda et al, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Phylogenetic groups B2 and D are commonly related to UPEC strains collected from patients with UTIs; however, at a lower frequency, these strains are also related to phylogenetic groups A and B1. In addition, multidrug-resistance (MDR) and virulence factors described in UPEC strains are associated with phylogenetic group B2 (Derakhshandeh et al, 2015; Ferjani et al, 2015). Recently, the MDR-phenotype was found to be related to phylogenetic groups A and D; although, UPEC strains susceptible to most antibiotics are also related to phylogenetic group B2 (Ejrnæs et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar study conducted by Kot et al [42], showed that 38.1% E. coli strains belonged to phylogenetic group B2, 35.3% to group D, 18.5% to group A, and 8.1% to group B1. Phylogenetic group A, represented 18% of isolates, which was higher than in studies conducted in South Korea 3.44% [39] and Iran 0.7% [47], but some studies found phylogroup A was the dominant phylogroup [9,15,48] suggesting that the colon may be the main reservoir for strains that cause urinary tract infections [9]. In some studies, phylogroup D was the dominant strain [25,49].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic determinants that are studied includes those coding for type 1 [12,[14][15][16].Specific primers were used to amplify sequences of the fim, pap, sfa/foc, afa, hly, cnf, and aer operons. Details of primer sequences and predicted sizes of the amplified products are given in Table 1.…”
Section: Detection Of Virulence Genes Of Uropathogenic Escherichia Colimentioning
confidence: 99%
“…Em uma feira popular do município de Currais Novos -RN foi realizada uma avaliação da qualidade de plantas medicinais adquiridas (31) O patógeno E.coli é um bacilo Gram negativo, causador de 80 a 90% das infecções no trato urinário; é um microrganismo comensal da microbiota intestinal (32) .…”
Section: Ausênciaunclassified